The Psychometric Properties of the Norwegian version of ADHD Rating Scale IV, Schoolversion (ADHD-RS-IV School) - Kornør, Hege; Bøe, Tormod (PsykTestBarn, 2011)
Description: ADHD-RS-IV School is a questionnaire to be completed by teachers to detect ADHD symptoms in children and adolescents. The questionnaire contains 18 items, each with four answer options. It takes less than 20 minutes to complete. Item scores are summed up to score the total scale and the two subscales. Those who administer the ADHD-RS-IV should have general training in test use, as well as a professional status as psychologist, physician, or other health workers or teachers with education at the master degree level. Literature search: Our systematic literature search identified three publications from three Norwegian studies. Psychometrics: None of the included publications contained norm, validity or reliability evidence for the ADHD-RS-IV School. Conclusion: There is no evidence for the psychometric properties of the Norwegian version of the ADHD-RS-IV School.